2008
DOI: 10.1247/csf.08019
|View full text |Cite
|
Sign up to set email alerts
|

Migratory Localization of Cyclin D2-Cdk4 Complex Suggests a Spatial Regulation of the G1-S Transition

Abstract: ABSTRACT. The association of the cyclin D-Cdk (DC) complex with retinoblastoma protein (pRb) is required for the G1-S transition of the cell cycle. Cyclin synthesis, nuclear localization and degradation are control mechanisms for the transition, but regulation of the DC complex nuclear import also contributes to the transition. Analysis of the timing of the G1-S transition in mammalian cell lines revealed acceleration with overexpression of cyclin D2 and Cdk4. Immunolocalization assays revealed that cyclin D2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…Furthermore, in our study, Ca v 3.1 knockdown resulted in increases in the expressions of MIS12, SYCP1 and CCND2 (which are thought to be involved in cell cycle progression) (42)(43)(44). Consequently, Ca v 3.1 may also suppress the cell cycle, thus inhibiting proliferation.…”
Section: Discussionsupporting
confidence: 50%
“…Furthermore, in our study, Ca v 3.1 knockdown resulted in increases in the expressions of MIS12, SYCP1 and CCND2 (which are thought to be involved in cell cycle progression) (42)(43)(44). Consequently, Ca v 3.1 may also suppress the cell cycle, thus inhibiting proliferation.…”
Section: Discussionsupporting
confidence: 50%
“…It has been reported that the CCND2/CDK4/p27 complex is required for nuclear translocation of CCND236. Since the expression levels of CDK4 and p27 were not influenced in shlinc00598 stable HEK293t cell lines (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 93%
“…G1/S phase transition is a major checkpoint for cell cycle progression [26]. Therefore, CDK2 and cyclin D2 were examined, CDK2 and cyclin D2 are the critical differently positive regulators during this transition [27,28]. Western blotting assay showed that CDK2 and cyclin D2 were partly suppressed in the siRNALAP3 group in the U87 and U251 cells.…”
Section: Discussionmentioning
confidence: 99%